Effects of Sleep on Word Pair Memory in Children – Separating Item and Source Memory Aspects - Wang, Jing-Yi; Weber, Frederik D.; Zinke, Katharina; Noack, Hannes; Born, Jan (Frontiers in Psychology, 2017)
Word paired-associate learning is a well-established task to demonstrate sleep-dependent memory consolidation in adults as well as children. Sleep has also been proposed to benefit episodic features of memory, i.e., a memory for an event (item) bound into the spatiotemporal context it has been experienced in (source). We aimed to explore if sleep enhances word-pair memory in children by strengthening the episodic features of the memory, in particular. Sixty-one children (8-12 yrs) studied two lists of word-pairs with 1 hour in between. Retrieval testing comprised cued recall of the target word of each word-pair (item memory) and recalling in which list the word-pair had appeared in (source memory). Retrieval was tested either after 1 hour (short retention interval) or after 11 hours, with this long retention interval covering either nocturnal sleep or daytime wakefulness. Compared with the wake interval, sleep enhanced separate recall of both word-pairs and the lists per se, while recall of the combination of the word-pair and the list it had appeared in remained unaffected by sleep. An additional comparison with adult controls (n = 37) suggested that item-source bound memory (combined recall of word-pair and list) is generally diminished in children. Our results argue against the view that the sleep-induced enhancement in paired-associate learning in children is a consequence of sleep specifically enhancing the episodic features of the memory representation. On the contrary, sleep in children might strengthen item and source representations in isolation, while leaving the episodic memory representations (item-source binding) unaffected.